A retrospective study of the antimicrobial susceptibility patterns of Klebsiella pneumoniae isolated from urine samples over a decade in South India - Neelambike Sumana, Mahadevaiah; Maheshwarappa, Yogeesh D.; G., Kalyani; Mahale, Rashmi P.; G. S, Sowmya; Raghavendra Rao, Morubagal; Shankaregowda, Ranjitha; Chitaragi, Vidyavathi B.; R., Deepashree; S. R., Sujatha; Murthy, Neetha S.; Satyasai, Badveti; et al. (Frontiers in Microbiology, 2025)
IntroductionUrinary tract infections (UTIs) are common bacterial infections with significant health implications. This study aimed to assess the antimicrobial susceptibility (AST) patterns of Klebsiella pneumoniae (KPN) isolated from urine samples over a decade (2014–2023).MethodsThe study analyzed Klebsiella pneumoniae isolates AST pattern from urine samples at a tertiary care hospital in Mysuru (Karnataka), South India using the VITEK-2 (bioMérieux, France) database.ResultsOf 73,283 urine samples, 21,362 (29.15%) showed significant bacterial growth. The most frequently isolated organism was Escherichia coli (n = 9,211, 43.11%), followed by Pseudomonas aeruginosa (n = 1,108, 5.18%) and K. pneumoniae (n = 920, 4.30%). Of the 920 K. pneumoniae isolates, 385 (41.84%) were carbapenem-resistant (CRKP). Isolation rates were higher in males (n = 229, 59.48%) than females (n = 156, 40.52%), with a statistically significant p-value (<0.0001). Carbapenem resistance rose from 3.70% in 2014 to 66.13% in 2021, then declined to 38.55% in 2023. Resistance to fluoroquinolones, aminoglycosides, and cephalosporins increased, with cephalosporin resistance exceeding 85% by 2023. These trends reflect growing drug resistance among K. pneumoniae.ConclusionThe study reveals a significant rise in antimicrobial resistance in Klebsiella pneumoniae, particularly to carbapenems and fluoroquinolones. Effective treatment requires antibiotic stewardship, strict infection control, and ongoing surveillance to maintain therapeutic options.